2021
DOI: 10.1039/d0sc06369j
|View full text |Cite
|
Sign up to set email alerts
|

A novel catalytic heme cofactor in SfmD with a single thioether bond and a bis-His ligand set revealed by a de novo crystal structural and spectroscopic study

Abstract: SfmD is a heme-dependent enzyme in the biosynthetic pathway of saframycin A. Here, we present a 1.78-Å resolution de novo crystal structure of SfmD, which unveils a novel heme cofactor...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…TDO belongs to a histidine-ligated heme dioxygenase superfamily, oxidizing tryptophan or tryptophan-derived substrates with a ferrous heme and molecular oxygen. Indoleamine 2,3-dioxygenase (IDO), PrnB, and MarE are also members of this enzyme family, and the former two have been structurally characterized. Recently, SfmD as a 3-methyl- l -tyrosine hydroxylase involved in the biosynthesis of saframycin has been identified and structurally resembles the TDO superfamily enzymes . Despite the conservation of the global tertiary fold, the overall rmsd values upon superposition of the structures are strikingly poor due to diverse structural topology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TDO belongs to a histidine-ligated heme dioxygenase superfamily, oxidizing tryptophan or tryptophan-derived substrates with a ferrous heme and molecular oxygen. Indoleamine 2,3-dioxygenase (IDO), PrnB, and MarE are also members of this enzyme family, and the former two have been structurally characterized. Recently, SfmD as a 3-methyl- l -tyrosine hydroxylase involved in the biosynthesis of saframycin has been identified and structurally resembles the TDO superfamily enzymes . Despite the conservation of the global tertiary fold, the overall rmsd values upon superposition of the structures are strikingly poor due to diverse structural topology.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, even though TyrH and SfmD catalyze the same Tyr-based, ortho -hydroxylation, they have distinct heme cofactors, binding domains, and relative positions (Figure S14). These enzymes may be related in an evolutionary perspective, considering TyrH and SfmD both exhibit slow oxygen-dependent hydroxylation activities in the presence of ascorbate, , while the TDO superfamily members can exhibit monooxygenation reactivity. , We expect to explore more biochemical implications of these related enzymes in the near future and thus, better understand the evolution and structure–function relationships among these histidine-ligated heme enzymes catalyzing aromatic amino acid oxygenation reactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently,a tomically-dispersed non-precious metal-N 4 (M-N 4 )m oieties anchored on pyrolyzed carbon (M-N 4 /C) catalysts have attracted much attention, [7] which show as ignificant impact on promoting the intrinsic CO 2 RR performance by facilitating the charge transfer from M-N x moieties to CO 2 molecular and then activating adsorbed CO 2 species. [8] Despite the most promising CO 2 RR activity obtained with M-N 4 /C catalysts,t heir catalytic performance still needs to be further improved for practical applications.C ompared to biological systems of heme-based enzymes (M-N 4 configuration), [9] it can be found that most of the currently reported M-N 4 /C catalysts are plane symmetrical structure, similar with phthalocyanine [10] or porphyrin structure. [11] Nevertheless,the plane symmetrical structure of the M-N 4 moieties usually faces ah ighreaction free energy for the water dissociation step,o wing to their sluggish proton-feeding kinetics in coupling with protons and electrons for CO production [Eqs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently,a tomically-dispersed non-precious metal-N 4 (M-N 4 )m oieties anchored on pyrolyzed carbon (M-N 4 /C) catalysts have attracted much attention, [7] which show as ignificant impact on promoting the intrinsic CO 2 RR performance by facilitating the charge transfer from M-N x moieties to CO 2 molecular and then activating adsorbed CO 2 species. [8] Despite the most promising CO 2 RR activity obtained with M-N 4 /C catalysts,t heir catalytic performance still needs to be further improved for practical applications.C ompared to biological systems of heme-based enzymes (M-N 4 configuration), [9] it can be found that most of the currently reported M-N 4 /C catalysts are plane symmetrical structure, similar with phthalocyanine [10] or porphyrin structure. [11] Nevertheless,the plane symmetrical structure of the M-N 4 moieties usually faces ah ighreaction free energy for the water dissociation step,o wing to their sluggish proton-feeding kinetics in coupling with protons and electrons for CO production [Eqs.…”
Section: Introductionmentioning
confidence: 99%